2016
DOI: 10.2169/internalmedicine.55.6314
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Coronary Artery Aneurysms and Thoracic Aortitis Associated with IgG4-related Disease

Abstract: A 60-year-old man was admitted due to the onset of right coronary artery (RCA) aneurysms. Coronary angiography showed two RCA aneurysms and focal stenosis with limitations in the blood flow. Balloon angioplasty was performed. However, the follow-up coronary angiography showed restenosis, an enlarged proximal aneurysm and a newly formed aneurysm. The serum immunoglobulin G4 level was elevated to 1,350 mg/dL and fluorodeoxyglucose positron emission tomography showed increased uptake in the ascending aorta, so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Cardiac surgery was necessary in three of the eight cases (6, 9-15, Table 2 ). All patients who had coronary stenosis or aneurysms were resistant to corticosteroid ( 6 , 9 - 15 ). In contrast, the patients without coronary stenosis or aneurysms responded to corticosteroid (18, the present case).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac surgery was necessary in three of the eight cases (6, 9-15, Table 2 ). All patients who had coronary stenosis or aneurysms were resistant to corticosteroid ( 6 , 9 - 15 ). In contrast, the patients without coronary stenosis or aneurysms responded to corticosteroid (18, the present case).…”
Section: Discussionmentioning
confidence: 99%
“…The pathological characteristics include diffuse lymphoplasmacytic infiltration, fibrosis, obliterative phlebitis, and eosinophilic infiltration in the involved organs ( 7 , 8 ). Many reports indicate that coronary artery involvement is related to a poor prognosis ( 6 , 9 - 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several cases have been reported that involved IgG4-related coronary disease. Some patients had pseudotumors surrounding coronary arteries (10)(11)(12)(13)(14), and others had aneurysms of coronary arteries (15)(16)(17)(18)(19)(20). The present patient had pseudotumors surrounding two coronary arteries with stenosis.…”
Section: Discussionmentioning
confidence: 50%
“…It may then be questioned whether the current patient can be diagnosed with IgG4-related disease that affected multiple cardiovascular tissues. In several previous reports, IgG4-related cardiovascular disease was diagnosed when either IgG4-positive plasmacytic infiltration or elevated serum IgG4 was present alongside the suspected radiologic findings, 5,14) or when IgG4-related disease-like radiologic findings were observed in the heart or vessels in association with IgG4-related disease diagnosed elsewhere in non-cardiovascular organs. 15,16) On the other hand, cur- rently, unlike several other organs, 17) cardiac valve-specific diagnostic criteria for the diagnosis of IgG4-related disease do not exist in Japan.…”
Section: Discussionmentioning
confidence: 99%